Prevalence, clinical and molecular characteristics of early stage EGFR-mutated lung cancer in a real-life West-European cohort: Implications for adjuvant therapy. (March 2023) - Hondelink, Liesbeth M.; Ernst, Sophie M.; Atmodimedjo, Peggy; Cohen, Danielle; Wolf, Janina L.; Dingemans, Anne-Marie C.; Dubbink, Hendrikus J.; von der Thüsen, Jan H.
Abstract: Objectives: The landmark ADAURA study recently demonstrated a significant disease-free survival benefit of adjuvant osimertinib in patients with resected EGFR -mutated lung adenocarcinoma. However, data on prevalence rates and stage distribution of EGFR mutations in non-small cell lung cancer in Western populations are limited since upfront EGFR testing in early stage lung adenocarcinoma is not common practice. Here, we present a unique, real-world, unselected cohort of lung adenocarcinoma to aid in providing a rationale for routine testing of early stage lung cancers for EGFR mutations in the West-European population. Material and methods: We performed routine unbiased testing of all cases, regardless of TNM stage, with targeted next-generation sequencing on 486 lung adenocarcinoma cases between 01- January 2014 and 01 February 2020. Clinical and pathological data, including co-mutations and morphology, were collected. EGFR- mutated cases were compared to KRAS- mutated cases to investigate EGFR- specific characteristics. Results: In total, 53 of 486 lung adenocarcinomas (11%) harboured an EGFR mutation. In early stages (stage 0-IIIA), the prevalence was 13%, versus 9% in stage IIIB-IV. Nine out of 130 (7%) stage IB-IIIA patients fit the ADAURA criteria. Early stage cases harboured more L858R mutations (p = 0.02), fewer exon 20 insertions (p = 0.048), fewer TP53 co-mutations (p = 0.007), and were more frequently never smokers (p = 0.04) compared to late stage cases with EGFR mutations. The KRAS -mutated cases were distributed more evenly across TNM stages compared to the EGFR- mutated cases. Conclusion: As (neo-)adjuvant targeted therapy regimes enter the field of lung cancer treatment, molecular analysis of early stage non-small cell lung cancer becomes relevant. Testing for EGFR mutations in early stage lung adenocarcinoma holds a substantial yield in our population, as our number needed to test ratio for adjuvant osimertinib was 14.4. The observed differences between early and late stage disease warrant further analysis to work towards better prognostic stratification and more personalised treatment. Highlights: EGFR mutation prevalence was 9% in early stage NSCLC in our West-European cohort. EGFR mutation prevalence is spread unevenly across TNM stages. Number needed to test for adjuvant osimertinib was 14.4 in our population. Early- and late stage EGFR -mutated NSCLC differs in clinicopathological features.